Strategi Peningkatan Kualitas Pembelajaran Melalui Gamifikasi: Studi Kasus Pelatihan Guru di Kabupaten Padang Pariaman - Nofrahadi; Afnita; Yulianti Rasyid; Dewi Anggraini; Farel Olva Zuve; Dewi Syafrina (IKIP PGRI Bojonegoro, 2025)
ABSTRACT Improving the quality of learning requires educators to adapt to innovative approaches, one of which is through gamification. This article aims to describe the implementation of gamification training for teachers in three schools (SMP N 1, 2, and 3 Batang Gasan) in Padang Pariaman Regency and analyze its impact on understanding, enthusiasm, perceptions of effectiveness, and the practice of applying gamification. This study used a one-group pretest-posttest design with 15 teachers as participants. The instrument, in the form of a Likert scale questionnaire, measured four main aspects, supplemented by an evaluation of training satisfaction. The four variables measured were understanding of gamification (scale 0–100), enthusiasm for innovation (scale 1–5), perception of the effectiveness of gamification (scale 1–5), and frequency of application of gamification techniques (scale 1–5). The data were analyzed descriptively and inferentially using a paired t-test. The results of the analysis showed a significant increase in all variables. The gamification understanding score increased from 58.7 ± 6.4 to 84.5 ± 5.8 (t=12.37; p<0.001). Enthusiasm for innovation rose from 3.2 ± 0.7 to 4.6 ± 0.5 (t=10.12; p<0.001), perception of gamification effectiveness from 3.4 ± 0.6 to 4.5 ± 0.4 (t=9.64; p<0.001), and frequency of gamification application from 2.1 ± 0.8 to 3.9 ± 0.6 (t=8.88; p<0.001). This improvement indicates that the training provided was successful in strengthening the cognitive, affective, and behavioral aspects of teachers related to the use of gamification in learning. Keywords: Gamification, Teacher Training, Pretest-Posttest, Learning Innovation, Learning Effectiveness ABSTRAK Peningkatan kualitas pembelajaran menuntut tenaga pendidik untuk beradaptasi dengan pendekatan inovatif, salah satunya melalui gamifikasi. Artikel ini bertujuan mendeskripsikan implementasi pelatihan gamifikasi bagi guru di tiga sekolah (SMP N 1, 2, dan 3 Batang Gasan) Kabupaten Padang Pariaman serta menganalisis dampaknya terhadap pemahaman, antusiasme, persepsi efektivitas, dan praktik penerapan gamifikasi. Penelitian ini menggunakan desain one group pretest-posttest dengan 15 guru sebagai peserta. Instrumen berupa angket skala Likert mengukur empat aspek utama, dilengkapi evaluasi kepuasan pelatihan. Empat variabel yang diukur adalah pemahaman gamifikasi (skala 0–100), antusiasme terhadap inovasi (skala 1–5), persepsi efektivitas gamifikasi (skala 1–5), dan frekuensi penerapan teknik gamifikasi (skala 1–5). Data dianalisis secara deskriptif dan inferensial menggunakan uji paired t-test. Hasil analisis menunjukkan peningkatan yang signifikan pada seluruh variabel. Skor pemahaman gamifikasi meningkat dari 58,7 ± 6,4 menjadi 84,5 ± 5,8 (t=12,37; p<0,001). Antusiasme terhadap inovasi naik dari 3,2 ± 0,7 menjadi 4,6 ± 0,5 (t=10,12; p<0,001), persepsi efektivitas gamifikasi dari 3,4 ± 0,6 menjadi 4,5 ± 0,4 (t=9,64; p<0,001), dan frekuensi penerapan gamifikasi dari 2,1 ± 0,8 menjadi 3,9 ± 0,6 (t=8,88; p<0,001). Peningkatan ini mengindikasikan bahwa pelatihan yang diberikan berhasil memperkuat aspek kognitif, afektif, dan perilaku guru terkait penggunaan gamifikasi dalam pembelajaran. Kata Kunci: Gamifikasi, Pelatihan Guru, Pretest-Posttest, Inovasi Pembelajaran, Efektivitas Pembelajaran